Relationship of academic performance and academic self-concept with career decision-making among UPM undergraduate students / Siti Nadhirah Mohd Zaini ... [et al.] - Mohd Zaini, Siti Nadhirah; Md Rami, Ahmad Aizuddin; Mohamad Arsad, Nurazidawati; Mohd Anuar, Mohd Ashraff (Universiti Teknologi MARA, 2021)
Choosing the right career paths relevant to their future is probably one of the most challenging decisions confronting the majority of adolescents. Hence, recognition of the factors affecting students' career decisions is more important than ever. This study aimed to investigate the effects of academic performance and academic self-concept in relation to career decision-making among UPM undergraduate students. A quantitative research design using a questionnaire was utilized. The questionnaire, one touching on academic self-concept and the other on career decision-making, was disseminated to the respondents via emails and through social network services in the form of Google Forms. For data on academic performance, the researcher based it on the students' current Cumulative Grade Point Average (CGPA) results. The Multi-stage cluster sampling method was employed to a total of 171 final-year undergraduates from Universiti Putra Malaysia (UPM). The data were analysed using SmartPLS 3. The result of partial least squares structural equation modelling (PLS-SEM) revealed that the students' academic self-concept directly and significantly affects their career decision-making. However, there is no direct relationship between academic performance and career decision-making. This study found that developing students' academic self-concept can assist them to decide on their career paths.